Assessment of Streptococcus mutans in healthy versus gingivitis and chronic periodontitis: A clinico-microbiological study - Sneha Dani; Ashwin Prabhu; K R Chaitra; N C Desai; Sudhir R Patil; Ranjan Rajeev (Wolters Kluwer Medknow Publications, 2016)
Background: Dental caries and periodontal disease are most common oral diseases. Streptococcus mutans are considered to be the major pathogens in initiation of dental caries. Evidence shows that periodontal disease and caries share a number of contributory factors. Thus in view of these findings it would be worthwhile to examine whether Streptococcus mutans persist within the saliva and subgingival environment of the periodontitis patients and to determine whether there is any association between Streptococcus mutans colonization, pH of saliva and sub-gingival plaque pH in periodontal diseases before therapy. Methods: The study comprises of 75 subjects aged between 20-70 years, reporting to department of Periodontology, KLEs Institute of Dental Sciences, Bangalore. Subjects were divided into 3 groups of 25 each. Group 1 - Healthy controls, Group 2 - Gingivitis Group, 3 - Chronic periodontitis. Unstimulated saliva was collected in sterile container and immediately pH was evaluated. Subgingival plaque samples were collected from four deepest periodontal pockets in chronic periodontitis and from first molars in healthy subjects using 4 sterile paper points. In gingivitis subjects samples were collected from areas showing maximum signs of inflammation. All paper points and saliva samples were cultured on mitis salivarius agar culture media with bacitracin for quantification of the Streptococcus mutans colonies. Results: Increased colonization of Streptococcus mutans was seen in chronic periodontitis subjects both in saliva and sub-gingival plaque samples. There was also a positive correlation seen with the periodontal parameters. Conclusion: More severe forms of periodontal disease may create different ecological niches for the proliferation of Streptococcus mutans.